Penelitian Terkini tentang Pengembangan Pemisahan dan Penangkapan Karbon dengan Membran Berbahan Dasar Polimer: Tinjauan Kebaruan - Siti Nurkhamidah; Dodi Eko Nanda; Retno Dwi Nyamiati; Daniel Timotius; Mahreni Mahreni; Dian Purnami Handayani; Dwi Amalia; Alfathony Krisnabudhi (Eksergi, 2023)
Separation and capture of carbon dioxide (CO2) has become a very hot topic of discussion recently. The increasing amount of carbon dioxide in the environment makes environmental pollution very significant. Membrane technology is one of the alternative carbon separation processes that are increasingly in demand, because membrane technology provides excellent advantages in terms of energy requirements used, capital investment invested, and ease of operating equipment compared to other processes. Many membrane constituent materials can be used to be the basic material for making membranes, including polymeric materials. This review discusses the various polymeric materials that can be used as basic materials for gas membranes in terms of plasticization, constituent components, flexibility, and mechanical strength. It also provides an understanding of alternatives to improve the properties of polymer-based membranes.